Cell-Fate Specification in Arabidopsis Roots Requires Coordinative Action of Lineage Instruction and Positional Reprogramming. Issue 2 (18th August 2017) - Yu, Qiaozhi; Li, Pengxue; Liang, Nengsong; Wang, Hong; Xu, Meizhi; Wu, Shuang
Abstract : Cell-fate determination in Arabidopsis roots utilizes lineage-dependent mechanisms at early stages and positional-dependent signaling at later stages. Abstract: Tissue organization and pattern formation within a multicellular organism rely on coordinated cell division and cell-fate determination. In animals, cell fates are mainly determined by a cell lineage-dependent mechanism, whereas in plants, positional information is thought to be the primary determinant of cell fates. However, our understanding of cell-fate regulation in plants mostly relies on the histological and anatomical studies on Arabidopsis ( Arabidopsis thaliana ) roots, which contain a single layer of each cell type in nonvascular tissues. Here, we investigate the dynamic cell-fate acquisition in modified Arabidopsis roots with additional cell layers that are artificially generated by the misexpression of SHORT-ROOT ( SHR ). We found that cell-fate determination in Arabidopsis roots is a dimorphic cascade with lineage inheritance dominant in the early stage of pattern formation. The inherited cell identity can subsequently be removed or modified by positional information. The instruction of cell-fate conversion is not a fast readout during root development. The final identity of a cell type is determined by the synergistic contribution from multiple layers of regulation, including symplastic communication across tissues. Our findings underline the collaborative inputs during cell-fate instruction.